Synthesis of Digital Two-Circuit Control Systems With Dynamic Correction for Arm Manipulator (Моделювання, керування та інформаційні технології, 2019)
The method of multicriterial parametric synthesis of two-circuit systems with discrete controllers in the space of parameters of their adjustment, including periods of discreteness of system contours is offered. The example that proves the effectiveness of this method was shown. The developed control system was applied to the simulation model of arm manipulator